2018
DOI: 10.1242/dev.160572
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal expression of a sterol biosynthesis gene regulates root growth by a non-cell-autonomous mechanism in Arabidopsis

Abstract: The epidermis is hypothesized to play a signalling role during plant development. One class of mutants showing defects in signal transduction and radial patterning are those in sterol biosynthesis. The expectation is that living cells require sterols, but it is not clear that all cell types express sterol biosynthesis genes. The HYDRA1 (HYD1) gene of Arabidopsis encodes sterol Δ8-Δ7 isomerase, and although hyd1 seedlings are defective in radial patterning across several tissues, we show that the HYD1 gene is e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 46 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…This phylogenetic context can be combined with future molecular genetic findings for greater insights. Knowing where and how those membrane protein complexes originate and are destined in the cell, and their dynamics and relationship with membrane composition that determines for example transporter polarity in a tissue-specific manner, 119 will improve our knowledge of the importance of SNARE complexes in vesicle trafficking pathways and in a range of developmental and stress response pathways in higher plants.…”
Section: Resultsmentioning
confidence: 99%
“…This phylogenetic context can be combined with future molecular genetic findings for greater insights. Knowing where and how those membrane protein complexes originate and are destined in the cell, and their dynamics and relationship with membrane composition that determines for example transporter polarity in a tissue-specific manner, 119 will improve our knowledge of the importance of SNARE complexes in vesicle trafficking pathways and in a range of developmental and stress response pathways in higher plants.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that a number of sterol mutants exhibit aberrant auxin response and polar auxin transport due to altered sterol composition [ 8 , 9 , 19 , 21 , 22 , 25 , 27 ]. However, whether a certain sterol component has a function in regulating auxin activity is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The cotyledon vascular patterning1 ( cvp1 ) mutant showed weak auxin insensitivity, and could enhance the auxin resistance of transport inhibitor resistant1 ( tir1 ) and auxin resistance1-3 ( axr1-3 ) mutants [ 9 , 24 ]. The smt1 , cpi1-1 , fk/hyd2, hyd1, smt2 smt3, smo2-1 smo2-2, and smo1-1 smo1-2 mutants displayed aberrant localizations of PIN-FORMED (PIN) auxin efflux carriers in seedling root or embryo [ 8 , 19 , 21 , 22 , 25 , 26 , 27 ]. It has been demonstrated that sterol endocytosis shares a common route with PIN2 recycling [ 28 ], and correct sterol composition was required for endocytosis of PIN2 for the establishment of its polar localization after cytokinesis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…This protein, designated MACCI-BOU 1 (MAB1), is a molecular player in auxin-regulated organ formation and has been suggested to contribute to PIN-dependent auxin polar transport via metabolic regulation. 46 The Arabidopsis homologue of tr_4377, AT1G20050, which encodes a 3-betahydroxysteroid-delta-isomerase, the integral membrane protein HYDRA1, which has been demonstrated to play an important role in root patterning and influence the distribution of the PIN1 and PIN2 auxin efflux carriers; 47 the abundance of tr_4377 transcripts was increased by OSRG. Two upregulated genes were homologous to Arabidopsis genes that show Blast hits only to plant species and encode proteins of unknown function: tr_12315, homologous to AT4G30010, which encodes an unknown plant-specific protein located in mitochondria according to SUBA4 (http://suba.live/), and tr_9407, homologous to AT1G70840, encoding major latex protein (MLP)-like protein 31.…”
Section: Differentially Expressed Genes After 6 H Of Cultivation Of Buckwheat Explants In Iaa-containing Medium With or Without Osrgmentioning
confidence: 99%
“…PBP1 contains EF-hand calcium-binding motifs and acts as a positive regulator of auxin release from cells by regulating the activity of the protein kinase PINOID, which phosphorylates conserved serine residues in PIN auxin efflux carriers. 76 The distribution of the auxin efflux carriers PIN1 and PIN2 and PIN-dependent auxin polar transport can also be influenced by the integral membrane protein HYDRA1, 47 by MACCI-BOU 1 (MAB1), 46 and by SAC2 and SRC2 proteins involved in vesicle trafficking to vacuoles 48,49 since degradation of at least some PIN proteins may occur through this trafficking route. 77 The transcription of the genes encoding listed proteins was affected by OSRG.Taken together, these results indicate that some elements of the auxin signaling pathway are influenced by the presence of oligosaccharin, as can be assumed from the differential expression of the corresponding genes.…”
Section: Modulation Of the Auxin Response By Osrgmentioning
confidence: 99%